2021
DOI: 10.1021/acs.cgd.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-like Packing Modes Facilitating High Thermal Stability: A Comparative Study in the Polymorphs of Planar Energetic Molecules

Abstract: Graphite-like packing structures have aroused the attention in the community of energetic materials because of their good balances between energy and safety. Nevertheless, the detailed relationship between different packing modes and performance is still lacking, leading to a handful of advanced graphite-like energetic materials. Here, five compounds with polymorphs containing graphitelike packing structures were screened out from over 1000 experimentally measured nitro crystals. As a comparative study, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It is reported that the stability of energetic molecules is closely related to their aromaticity. , For a better understanding of the relationship between the characters of the molecular structures and their stabilities, the aromaticities of compounds C1 and C2 were calculated and discussed. In Figure a,b, the green and blue isosurfaces show the area where compounds C1 and C2 produce 2.00 ppm of shielding and deshielding to the external magnetic field in the Z direction, respectively. A shielded area is observed around the central skeletons of C1 and C2 , whereas the deshielded area is located at the peripheral zones of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the stability of energetic molecules is closely related to their aromaticity. , For a better understanding of the relationship between the characters of the molecular structures and their stabilities, the aromaticities of compounds C1 and C2 were calculated and discussed. In Figure a,b, the green and blue isosurfaces show the area where compounds C1 and C2 produce 2.00 ppm of shielding and deshielding to the external magnetic field in the Z direction, respectively. A shielded area is observed around the central skeletons of C1 and C2 , whereas the deshielded area is located at the peripheral zones of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Layered packing structures of energetic materials (EMs) can effectively buffer against externally mechanical stimuli by interlayer slipping, leading to a better energy and safety (E&S) balance than other packing modes. However, the rational design of layered energetic crystals is still a challenge due to the complicated intermolecular interactions and the difficulties of accurate prediction of crystal structure, limiting the design of EMs mainly at the molecular level, such as the permutation and combination between various parent rings (i.e., benzene and oxadiazole) with functional groups (i.e., nitro, amino, and azide groups). Furthermore, a minor modification of molecules changes the crystal structures and performances (especially for impact sensitivity) greatly in most cases, which increases the difficulty of constructing layered energetic crystals. , As a result, only a handful of advanced layered EMs exist are present, most of which were accidentally discovered in experiments …”
Section: Introductionmentioning
confidence: 99%
“…14−16 Very recently, reactive molecular dynamics simulations have suggested that a layered packing fashion always exhibits the highest apparent activation energies of the initial decomposition reactions than other packing modes in the same energetic compounds with polymorphs. 17 Therefore, layered energetic crystals attract much attention currently due to their well-balanced detonation performance and mechanical sensitivity. 10,12 Compared with the existing molecular design method of EMs, layered packing modes involve complex intermolecular interactions, making it difficult to design layered energetic crystals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Crystal engineering aims to clarify the relationships between molecules, crystals, and properties and further utilize these relationships to design and prepare novel materials with desired physical and chemical properties, which are widely used in many solid materials, such as drugs, , organic semiconductors, , and metal–organic frameworks. , In the field of energetic materials (EMs), crystal engineering has been regarded as an effective approach in recent years to alleviate the contradiction between energy and safety performances since special packing modes can possess both high energy and low sensitivity, especially the layered packing structures. On the one hand, statistical analysis shows that layered energetic crystals have relatively high packing coefficients, which benefit in increasing crystal densities and detonation performances. On the other hand, the layered packing structures can buffer against external stimuli by interlayer slipping, contributing to low mechanical sensitivities. Very recently, reactive molecular dynamics simulations have suggested that a layered packing fashion always exhibits the highest apparent activation energies of the initial decomposition reactions than other packing modes in the same energetic compounds with polymorphs . Therefore, layered energetic crystals attract much attention currently due to their well-balanced detonation performance and mechanical sensitivity. , …”
Section: Introductionmentioning
confidence: 99%